Assessment of Bite Force in Patients Treated with 2.0-mm Traditional Miniplates versus 2.0-mm Locking Plates for Mandibular Fracture. Issue 1 (March 2016) - Rastogi, Sanjay; Reddy, MahendraParvath; Swarup, AzeezGaurav; Swarup, Divya; Choudhury, Rupshikha
The objective of this study is to analyze the difference in bite forces in patients treated for mandibular fractures with 2.0 mm conventional and locking titanium plating system. A randomized study was performed for the treatment of fractures of mandible. In this study, 20 adult patients with isolated mandibular fracture were included. The patients were randomly allocated into two groups, that is, Group I-2.0 mm nonlocking (traditional) and Group II-2.0 mm locking plates. Bite force was evaluated at 1st, 3rd, and 6th weeks. Comparison of all the assessed parameters between both the groups depicted no significant difference in terms of pain, swelling including the incidence of infection, paresthesia, and hardware failure. Although same was true in case of bite force between both the groups at various time intervals, there was statistically significant increase in the bite force within the group comprising patients in whom locking plates was used between 1st and 3rd weeks follow-up period and highly significant increase in bite force between 1st and 6th weeks of follow-up period. The rapid improvement of bite force values when locking plates were used implies that the locking plate can be used in preference to conventional plates to achieve early mobilization with assured stability in the treatment of mandibular fractures.